Anomalous right coronary artery origin, arising from the high anterior wall of the right coronary artery sinus of Valsalva in a patient with acute ST-elevation myocardial infarction - Ali Khorram, Sokhrab Mohammed; Jith, Akhil (Indian Journal of Case Reports, 2025)
Anomalous origin of the high take-off right coronary artery (RCA) arising from the anterior wall of the right sinus of Valsalva is rare and can pose extreme challenges for the operator, especially in the setting of acute myocardial infarction (MI). Herein, we describe a patient in whom this very rare anomaly was encountered in a setting of acute anterior wall MI with the involvement of the inferior wall. Since we were aware of the RCA anomalies, as we had recently encountered a case of another RCA anomaly with the RCA ostium arising from the left coronary sinus, in a relatively elective case, we could successfully manage this case in the acute emergent setting of ST-elevation MI, minimizing contrast load and avoiding complications. Rapid recognition of this congenital anomaly and selection of an appropriate guide catheter were keys to achieving timely reperfusion and a good outcome in this case.